Evaluation of Imaging Utilization Prior to Referral of Musculoskeletal Tumors: A Prospective Study. (7th January 2015) - Nystrom, Lukas M.; Reimer, Nickolas B.; Dean, Cooper W.; Bush, Charles H.; Scarborough, Mark T.; Gibbs, C. Parker
Abstract : Background: Imaging studies are essential when evaluating a patient with a musculoskeletal neoplasm, and they represent a potential waste of resources when used inappropriately. The objective of this study was to prospectively evaluate a consecutive series of patients for inappropriate utilization of imaging prior to referral to a tertiary care facility. Our hypothesis was that advanced imaging is overutilized prior to referral of musculoskeletal neoplasms to a tertiary care center. Methods: All new patients referred for evaluation of a musculoskeletal neoplasm were prospectively analyzed over a three-month time period. All pre-referral imaging studies were recorded, including radiographs, computed tomographic scans, magnetic resonance imaging scans, bone scans, and 18-fluorodeoxyglucose positron emission tomography scans. Studies were reviewed by two musculoskeletal radiologists and two orthopaedic oncologists and were defined with use of specific preselected criteria as inappropriate if they were not indicated for diagnosis or treatment, if they required repeating because of excessive time since the study was obtained, or if they had poor image quality or technique. Results: We evaluated 298 consecutive patients (550 imaging studies). The inappropriate utilization rate was 1.5% (three of 204) for radiographs, 36.5% (twenty-three of sixty-three) for computed tomographic scans, 26.7% (fifty-six of 210) for magnetic resonance imaging scans, 45.1% (twenty-three of fifty-one) bone scans, and 45.5% (ten of twenty-two) for positron emission tomography scans. The overall inappropriate use of advanced imaging (magnetic resonance imaging, computed tomography, bone scan, positron emission tomography) was 32.4% (112 of 346 images). With regard to inappropriate use of magnetic resonance imaging, there was no difference between orthopaedic surgeons (28.2%) and primary care physicians (26.5%). Conclusions: Our data indicate a high prevalence (32.4%) of inappropriate advanced imaging of musculoskeletal tumors prior to referral. This represents a substantial cost to the patient and health-care system, a potential delay of referral, an increase in radiation exposure, and identification of other incidental findings.